PENGARUH MOTIVASI, TINGKAT PENDIDIKAN, DAN SOSIALISASI DALAM MENDORONG KEMAUAN WAJIB PAJAK MENGIKUTI PENGAMPUNAN PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Manado) - Assa, Kartini Merdekawati; Morasa, Jenny; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Tax Amnesty is an Indonesian government’s program that aims to accelerate Indonesian economy through wealth transfer and tax ransom payment from the taxpayers. The tax amnesty is tax abolition that should be owed, not subjected to administrative sanctions and tax penalties by reveal the wealth and pay the ransom. The objective of this study is to determine the influence of motivation, education level and socialization on the willingness to participate in tax amnesty in Manado Tax Office. This study used multiple linear regression method with SPSS version 20.0. The population is taken from the taxpayer that participated tax amnesty program in Manado Tax Office and the sample used in this study amounted to 100 taxpayers. The result showed that motivation, education level and socialization have an influence on the willingness to participate in tax amnesty.Keywords: motivation, education level, socialization, tax amnesty